2023
DOI: 10.3389/fpsyt.2023.1244164
|View full text |Cite
|
Sign up to set email alerts
|

Problem behaviours and caregiver burden among children with Autism Spectrum Disorder in Kuching, Sarawak

Shi Yi Chua,
Fairuz Nazri Abd Rahman,
Selvasingam Ratnasingam

Abstract: ObjectiveCaregivers of children with Autism Spectrum Disorder (ASD) often experience emotional and psychological distress, as well as disruptions to family life and employment due to the challenges of caring for children with ASD. This study examines the relationship between problem behaviours and caregiver burden among children with ASD.MethodA cross-sectional study using convenience sampling recruited 230 caregivers of children with ASD aged 4 to 18 years from selected autism centres in Kuching, Sarawak. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Regarding the study population, there was a notable lack of population-based studies (only 7% of the investigations: ABC: Chua et al, 2023;Rohacek et al, 2023 Deniz & Toseeb, 2023;Milosavljevic et al, 2016;Totsika et al, 2013), with the majority being convenience samples with participants recruited from clinics and other preexisting services. A significant proportion of the papers (26%; n = 43) relied on parent-reported clinical autism diagnoses or diagnoses derived from enrollment in schools for autistic people (see Appendix F for the risk of bias assessment).…”
Section: Mh Assessment Instrumentsmentioning
confidence: 99%
“…Regarding the study population, there was a notable lack of population-based studies (only 7% of the investigations: ABC: Chua et al, 2023;Rohacek et al, 2023 Deniz & Toseeb, 2023;Milosavljevic et al, 2016;Totsika et al, 2013), with the majority being convenience samples with participants recruited from clinics and other preexisting services. A significant proportion of the papers (26%; n = 43) relied on parent-reported clinical autism diagnoses or diagnoses derived from enrollment in schools for autistic people (see Appendix F for the risk of bias assessment).…”
Section: Mh Assessment Instrumentsmentioning
confidence: 99%
“… Peng et al (2023) used a Chinese version of the Family Questionnaire and found that in China, parents or spouses scored higher in emotional over involvement with schizophrenia patients compared to siblings, but no significant difference existed between fathers, mothers, or spouses. Secondly, most existing studies concentrated on the characteristics or correlations of factors influencing caregivers’ quality of life, lacking research on specific issues such as the impact of caregiver’s mental health burden ( Srivastava, 2005 ; Chua et al, 2023 ). Additionally, the number of research interviewees or samples typically does not exceed 500 ( Reinhard and Horwitz, 1995 ; Knock et al, 2011 ; Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%